Counselling With Primary School Children: A Personal Construct Theory Approach to Group Counselling (Journal of Advances and Scholarly Researches in Allied Education, 2011)
A model of group work, based onpersonal construct theory, was developed for children aged between 8 to 12years, attending school. Integrating the psychological needs of the children,counsellor skills and expertise, and criteria needed for treatment research,data were sought on changes to construing and behaviour, and on groupprocesses, before and after the intervention. The rationale behind the use ofthese outcome measures is provided, along with a discussion of the results. Thetreatment efficacy and clinical utility of this approach, as necessarydimensions of evidence-based  practice,are discussed.  Finally, the clinicalimplications of this counselling treatment approach with primary schoolchildren, is explored.